Assessment of Serum Vit D and Serum Ferritin in Female Pattern Androgenic Alopecia - Khalid Ibrahim Jasim; Abdul Satar Mohammed Ali Khidhair; Ghassan A Hussain (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Androgenic Alopecia (AGA) is a non-scarring alopecia that affects both men and women. Itis characterized by a progressive miniaturization of hair follicles with a characteristic pattern distribution ingenetically predisposed men and women.Aim of the study: To assess the level of serum ferritin and vit D3 in female pattern of androgenic alopecia.Patients and method: A prospective case control study carried out at Department of Dermatology inBaladgeneral hospital, Iraq at the period from the first of January 2019 to the end of Dec 2019.Results: serum vit D3 for patients was (22.8 ± 11.5) in case group and (34.4±5.7) in control group, whilefor S. ferritin was (35.7±5.0) in control group and (44.8±7.3) in control group. Vit D3 deficiency (<20 mg/dl) were found in 68% of patients while 30% with vit D3 insufficiency.In three grades of severity, it was found that vit D3 level in grade I was (24.2±6.9), in grade II (20.7±7.2),and in III (18.9±9.2). While for ferritin was (37.4±10.8) in grade I, (30.7±9.4) in grade II, and (25.9±12.1)in grade III.No significant differences were found between the three grades groups regarding serum vitamine D3, whilesignificant difference present among S. ferritin. The sensitivity of the vit D3 test to predict the disease were(90.9%), the specificity was excellent (95.1%), while for ferritin the sensitivity was (88.3%), the specificitywas (89.0%).Conclusion: Serum Vit D3 and Ferritin concentrations were significantly decrease in female with androgenicalopecia.